Comparison of Regulations on Medical Professional Discipline Enforcement Institutions between the United States, the United Kingdom, Singapore and Indonesia - Sudarmanto, Alif Muhammad; Nurmardiansyah, Eko; Nugroho, Hari Pudjo; Siregar, Rospita Adelina (Universitas Airlangga, 2025)
Law Number 17 of 2023 on Health served as a momentum for evaluation of the regulation regarding ethics and professional discipline enactment body for medical personnel, which includes doctors and dentists. The purpose of this research is to provide comparisons from regulations in the United States, Great Britain, Singapore, and Indonesia as an evaluation tool. Through doctrinal law method with analytical and comparative approach toward secondary data, this research found that there were notable regulation differences between the countries which could provide input for Indonesia. Analysis of professional discipline enactment body gave two key messages. One, Indonesia could give provisions on what could be subject to disciplinary actions, including legal violations that may be subject to disciplinary actions, in order to clarify the relationship between professional discipline and law. Two, Indonesia could introduce a tiered mechanism in the investigation of alleged professional discipline violations to strengthen the realm of professional discipline and affirm its position as primum remedium.